2015
DOI: 10.3892/mmr.2015.3215
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-101 attenuates hypoxia/reoxygenation-induced apoptosis through induction of autophagy in H9c2 cardiomyocytes

Abstract: Abstract. Autophagy is a cellular self-catabolic process responsible for the degradation of proteins and organelles. Autophagy is able to promote cell survival in response to stress, and increased autophagy amongst cardiomyocytes has been identified in conditions of heart failure, starvation and ischemia/reperfusion. However, the detailed regulatory mechanisms underlying autophagy in heart disease have remained elusive. MicroRNAs (miRNAs) have been implicated in the regulation of autophagy in cells under stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
(35 reference statements)
3
21
0
Order By: Relevance
“…Rat cardiac fibroblasts express miR-101, a regulator of ATG4, and expression is decreased under hypertrophic conditions as well as in the peri-infarct area 4 weeks after MI, however, TGF-β1 was identified as the target in this study (30, 75, 106). While they did not identify an autophagic target, this does not rule out autophagy’s involvement, and aligns with Wu et al findings in hypoxia/reoxygenation (H/R) studies with H9c2 cells (106,107). …”
Section: Autophagy and Cardiovascular Diseasesupporting
confidence: 70%
See 2 more Smart Citations
“…Rat cardiac fibroblasts express miR-101, a regulator of ATG4, and expression is decreased under hypertrophic conditions as well as in the peri-infarct area 4 weeks after MI, however, TGF-β1 was identified as the target in this study (30, 75, 106). While they did not identify an autophagic target, this does not rule out autophagy’s involvement, and aligns with Wu et al findings in hypoxia/reoxygenation (H/R) studies with H9c2 cells (106,107). …”
Section: Autophagy and Cardiovascular Diseasesupporting
confidence: 70%
“…Compensatory administration of miR-188-3p prevents death and minimizes infarct size in murine models of MI (78). It was reported by Wu et al that miR-101 is down regulated when H9c2 cells are treated under hypoxia/reoxygenation conditions and undergo apoptosis (107). They looked at the role of RAB5a in regulating autophagy and found that inhibition of miR-101 prevented apoptosis and elevated levels of autophagy (107).…”
Section: Autophagy and Cardiovascular Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of miR-101 was shown to attenuate hypoxia/ reoxygenation-induced apoptosis through induction of autophagy in H9C2 cardiomyocytes [41]. In another study, the level of miR-101-3p was significantly higher in heart transplant recipients with histologically verified acute cellular rejection compared with a control group and could discriminate between patients with and without allograft rejection [42].…”
Section: Discussionmentioning
confidence: 90%
“…Regulation of the miR-101/MAPK pathway plays an important role in proliferation and metastasis of gallbladder carcinoma [47], in LPS-activated Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry macrophages [48], in systemic lupus erythematosus [49] and in proliferation and migration of cardiac fibroblast [50]. Wang et al found that inhibition of miR-101could attenuate H9C2 apoptosis induced by hydrogen peroxide [41]. Thus, future studies are warranted to elucidate effects of dexmedetomidine on the miR-101/MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%